Measles Outbreak Associated With Low Vaccine Effectiveness Among Adults in Pohnpei State, Federated States of Micronesia, 2014 - Hales, Craig M. (Open Forum Infect Dis, 2016)
Background. A measles outbreak in Pohnpei State, Federated States of Micronesia in 2014 affected many persons who had received ≥1 dose of measles-containing vaccine (MCV). A mass vaccination campaign targeted persons aged 6 months to 49 years, regardless of prior vaccination. Methods. We evaluated vaccine effectiveness (VE) of MCV by comparing secondary attack rates among vaccinated and unvaccinated contacts after household exposure to measles. Results. Among 318 contacts, VE for precampaign MCV was 23.1% (95% confidence interval [CI], −425 to 87.3) for 1 dose, 63.4% (95% CI, −103 to 90.6) for 2 doses, and 95.9% (95% CI, 45.0 to 100) for 3 doses. Vaccine effectiveness was 78.7% (95% CI, 10.1 to 97.7) for campaign doses received ≥5 days before rash onset in the primary case and 50.4% (95% CI, −52.1 to 87.9) for doses received 4 days before to 3 days after rash onset in the primary case. Vaccine effectiveness for most recent doses received before 2010 ranged from 51% to 57%, but it increased to 84% for second doses received in 2010 or later. Conclusions. Low VE was a major source of measles susceptibility in this outbreak; potential reasons include historical cold chain inadequacies or waning of immunity. Vaccine effectiveness of campaign doses supports rapid implementation of vaccination campaigns in outbreak settings.